Electing a Rector in Brazil: Complicated Politics - Knobel, Marcelo (International Higher Education, 2021)
This article describes the succession process of the president (rector) of one of the most important public universities in Brazil. Although each public higher education institution in Latin America has a different election system, general patterns apply. The intricate election system that precedes formal appointment has positive and negative facets, which are important arguments in the discussion on improving governance—so necessary not only in public Latin American universities, but also worldwide.